Differences in the incidence of cirrhosis-associated complications between MASLD, MetALD and ALD among patients with decompensated liver cirrhosis - Laura Buttler; Anja Tiede; Marie Griemsmann; Hannah Rieland; Jim B. Mauz; Heiner Wedemeyer; Markus Cornberg; Tammo L. Tergast; Katharina L. Hupa-Breier; Benjamin Maasoumy (PLoS ONE, 2025)
Background Recently, the new definition of steatotic liver disease (SLD) has been introduced, which not only differentiates MASLD (Metabolic Dysfunction-Associated steatotic liver disease) from alcohol-related steatotic liver disease (ALD), but also introduces the concept of metabolic and alcohol-related SLD (MetALD). However, potential differences of the new etiologies regarding the clinical phenotype of patients with advanced liver cirrhosis still remain undetermined. Therefore, we analyzed survival and the incidence of cirrhosis-related complications in SLD-patients with advanced liver cirrhosis. Methods A number of 416 consecutive patients with MASLD, MetALD- and ALD-associated decompensated liver cirrhosis were investigated. Overall survival, infections, hepatic encephalopathy, portal-hypertensive bleeding, rehospitalization and development of hepatocellular carcinoma were retrospectively analyzed within one year of follow-up. Cox regression analyses were performed for survival, competing risk analyses for the cirrhosis-specific complications. MASLD was used as reference group. Results ALD was associated with a lower risk of infections (HR = 0.55; p < 0.001) compared to MASLD. This remained significant after adjustment for age, sex, Model for End-Stage Liver Disease (MELD), serum-sodium, serum-cholinesterase, diabetes, body mass index and norfloxacin (HR = 0.59; p = 0.02) in the multivariable competing risk model. Notably, the incidence of infections in MetALD patients was in between both groups (MetALD: 68.7%, ALD: 56.1%, MASLD: 87.3%). However, there were no differences in survival (MetALD: HR = 1.03; p = 0.93; ALD: HR = 0.79; p = 0.49) and the other complications studied here. Conclusion The risk of infections is increased in MASLD-associated cirrhosis compared to other SLD-phenotypes. Thus, the role of a metabolic risk profile should not be neglected even in patients with decompensated liver cirrhosis.